2017
DOI: 10.4209/aaqr.2015.10.0610
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the WRF-Chem Model with Different Physical Parameterization Schemes during an Extremely High PM2.5 Pollution Episode in Beijing

Abstract: To understand the impacts of different combinations of planetary boundary layer (PBL), short-wave (SW) and longwave (LW) radiation schemes on the simulation results of meteorological variables and PM 2.5 concentrations under extremely heavy pollution conditions, the Weather Research and Forecasting model with Chemistry (WRF-Chem) model was applied in Beijing to investigate a high PM 2.5 pollution episode that occurred in January, 2013. Four PBL schemes, two SW schemes and three LW schemes with a total of 12 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Chow et al, 2006;Herner et al, 2006;Pun et al, 2009;Ying and Kleeman, 2009;Zhang et al, 2010;Chen et al, 2014;Hasheminassab et al, 2014;Kelly et al, 2014;Baker et al, 2015;Brown et al, 2016). CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization) and IM-PROVE (Interagency Monitoring of Protected Visual Environments) observations show that dust is a primary contributor to the aerosols in the SJV, especially in the warm season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chow et al, 2006;Herner et al, 2006;Pun et al, 2009;Ying and Kleeman, 2009;Zhang et al, 2010;Chen et al, 2014;Hasheminassab et al, 2014;Kelly et al, 2014;Baker et al, 2015;Brown et al, 2016). CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization) and IM-PROVE (Interagency Monitoring of Protected Visual Environments) observations show that dust is a primary contributor to the aerosols in the SJV, especially in the warm season.…”
Section: Discussionmentioning
confidence: 99%
“…The Yonsei University (YSU) planetary boundary layer (PBL) scheme (Hong et al, 2006) is used in all of the simulations, except one sensitivity experiment that uses the ACM2 (Asymmetric Convective Model with non-local upward mixing and local downward mixing; Pleim, 2007) PBL scheme (referred to as "20km_P7" hereafter, Table 1). Previous studies showed that both the YSU and ACM2 schemes have good performance in simulating boundary layer properties (e.g., Hu et al, 2010;Xie et al, 2012;Cuchiara et al, 2014;Banks and Baldasano, 2016;Banks et al, 2016;Chen et al, 2017). Sub-grid convection, convective transport of chemical constituents and aerosols, and wet deposition from sub-grid convection are parameterized using the Grell 3-D ensemble cumulus scheme (Grell and Devenyi, 2002) in the 20 km simulations, while convective processes are resolved in the 4 km simulations.…”
Section: Model Description and Experiments Setupmentioning
confidence: 99%
“…This parameter in the studies carried out in the summer season by [65] and [60] were −31.84% and −18.5% respectively. The mean normalized bias (NMB) in [73].…”
Section: Pm25 Spatial Distribution Characteristicsmentioning
confidence: 99%
“…This model significantly reduces the inconsistency between meteorological and chemical processes and also takes feedback effects related to aerosol into account (Zhang et al, 2010;Chen et al, 2017). Nevertheless, the accurate modeling of aerosol feedback effects requires a reliable reproduction of the main driving process of the fate of atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%